Unterschiede noch sehr groß. ÖPNV im sächsisch-polnischen Grenzraum: Status quo und Perspektiven. - Ahrens, Gerd-Axel; Schöne, Marzena (Deutscher Verkehrs-Verl., 2006)
Grenzüberschreitende Vernetzung des ÖPNVs wird seit der EU-Erweiterung verstärkt in den entsprechenden Grenzräumen angestrebt. Dabei stoßen verschiedene Verwaltungs-, Planungs- und Rechtssysteme, wirtschaftliche Verhältnisse und Zahlungsbereitschaften aufeinander. Für die zeitnahe Nutzung der Chancen und Möglichkeiten aus der EU-Osterweiterung ist die Aufbereitung der derzeitigen bzw. geplanten nationalen Organisationsformen und der gesetzlichen Rahmenbedingungen im Grenzraum hilfreich. difu

There are still notable differences in the organisation of, and law parameters for, the ÖPNV (local public transport systems) of Saxony and Poland. In Poland there are no key plans for a comprehensive integrated system due to an apparent lack of appreciation of such a requirement. Poland's ÖPNV does not have the organizational framework that would correspond to the tasks, which Germany's integrated public transport system is entrusted with. Poland's SPNV and ÖSPV transport systems are not the actual carriers and have no influence on the range of services on offer. Obvious differences relating to the economic viability or socio-economic obligations of public transport are not identified. Disparities in the areas of organization and law parameters make it more difficult to achieve trans-border cooperation and regional integration of the ÖPNV systems. Furthermore, there are language barriers, also differences in economic capacity and income in addition to factors related to past levels of development. Future changes may be anticipated in connection with the proposed ÖPNV law for Poland, adjustment to EU specifications and organizational restructuring. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Grenzraum; Verkehrsplanung; Verkehrsprognose; Verkehrsinfrastruktur; Grenzüberschreitender Verkehr; EU-Erweiterung